Heterogeneous Organocatalysts Based on a Triazine‐Triazole Silane Ligand. Issue 38 (23rd September 2018) - Cruz, Paula; Pérez, Yolanda; del Hierro, Isabel
Abstract : Robust and non‐air‐sensitive metal‐free triazine‐triazole heterogeneous organocatalysts were prepared. The synthetic procedure involved the co‐condensation of a bridged tris silane precursor with tetraethyl orthosilicate (TEOS) in the presence of cetyltrimethylammonium bromide (CTAB). In addition, the silane precursor was anchored post‐synthesis onto mesoporous silica nanoparticles and used to stabilize magnetic nanoparticles. The organocatalysts were characterized by X‐ray diffraction (XRD), X‐ray fluorescence (XRF), N2 adsorption‐desorption, transmission electron microscopy (TEM), solid‐state nuclear magnetic resonance spectroscopy (CP‐MAS‐NMR), Fourier‐transform infrared spectroscopy (FT‐IR), and UV/Vis diffuse reflectance spectroscopy (DRUV/Vis). All materials, recoverable and recyclable, possess good catalytic activity in Knoevenagel condensation and in the one‐pot three‐component reaction for the synthesis of 2‐amino‐chromene derivatives under mild conditions. Abstract : Ordered organic‐inorganic hybrid materials were prepared by using a triazine‐triazole silane ligand consisting of an organic multifunctional linker placed between three silicon atoms, with structure R[Si(OEt)3 ]3, synthesized by a click chemistry reaction These materials are effective, robust, and stable heterogeneous organocatalysts in Knoevenagel and multicomponent condensation reactions under mild conditions.